Made in Florida - Courtney, David W.; Jacobs, Joseph; Miller, Margaret A. (Tampa : USF Art Museum - University of South Florida, 1989)
Alfonzo, Carlos ; Anuszkiewicz, Richard ; Bell, Harriet ; Calvo, Robert ; Chamberlain, John ; Fichter, Robert W. ; Hanson, Duane ; Henry, John ; Kipp, Lyman ; Kleinhard, Alexandra ; Larsen, Mernet ; Petersen, Robert ; Rauschenberg, Robert ; Roche, Jim ; Rosenquist, James ; Ruiz, Gilberto ; Saff, Donald ; Schneider, Deborah ; Theile, Robert ; Turkle, Tyler ; Wujcik, Theo ; Young, Purvis
Made in Florida, USF Art Museum - University of South Florida, Tampa, Florida USA, March 11 - June 3, 1989
kunstcatalogus
Keywords: Florida